A produção de conhecimento negra na psicologia da UFRGS : vozes negras que questionam a colonialidade do ser e do saber no contexto da Educação das Relações Étnico-Raciais - ERER - Nogueira, Fernanda (2021)
With the advent of the policy of racial quotas in Brazilian Federal Universities, the expansion of the entry of black students has changed the historical panorama of limited access, at which time black subjects begin to problematize the symbolic and material structures of the institution. One of these guidelines is the direction of knowledge production in undergraduate education. As a researcher at UFRGS, which is part of the follow-up of the affirmative action program of this university, and is placed as a white woman in the anti-racist struggle, I carried out this thesis in order to know what knowledge production has been mobilized by black and black students in the Psychology Course of UFRGS in the context of The Education of Ethnic-Racial Relations-ERER. The study follows the methodological precepts of cartography as an intervention research, in which knowledge is constructed with the subjects participating in the field investigated. The methodological instruments that supported were the observant participation, from which the experiences of being together were recorded in a logbook. Individual interviews and conversations were conducted with thirteen subjects from the Institute of Psychology, recorded and transcribed. The field research was developed in 2019 in the macro institutional space of UFRGS (Seminars of Education for Ethnic-Racial Relations in Curricula) and in the micro institutional space (Psychology Course). The analyses were carried out in the course of the research and, at its end it was subsidized by the Textual Analysis Discursive-ATD. The theoretical field that anchors the study is the Latin American decolonial studies, having as main theorists Boaventura de Souza Santos and Nilma Lino Gomes, as well as black intellectuals who problematize ethnic-racial relations in the contemporary. The findings point to a timid service by UFRGS to ERER legislation in the curricular structure of contents and themes in specific disciplines in undergraduate teaching. In the discussions for the implementation of ERER in the macro institutional space, among the various tensions observed among the academic subjects, we highlight the epistemic hierarchy in which the ERER contents are delegitimized from being present in basic professional education. There is an expectation by the community of greater commitment of the management bodies of UFRGS undergraduate in the composition of an institutional project of ERER, as well as for the commitment of the university to the ethnic-racial formation of intellectuality in the plot of relations of knowledge and racism. The production of knowledge that has been mobilized by black and black students in the Psychology Course is a black production that questions the Coloniality of Human. It opposes the inequalities present in racialized relationships subordinate and inferior Brazilian black lives, and that reproduce institutionally. Also tensions by intervention in the processes of production and reproduction of black existence in a white and Eurocentred institution, by means of pedagogical interventions, that seek the re-education of ethnic-racial relations, in addition to recognizing and confronting institutional racism. It is a black production that questions the Coloniality of Knowledge, which denounces the epistemicide of black scientific knowledge in the field of Psychology, and tensions by the possibility of being black subjects producing black knowledge. It is a production of authorial black knowledge, which culminates with the curricular change and the implementation of anti-racist practices and projects, which are now assumed by the management of the Psychology Course. Black voices, that increasingly calls on the university to diversify its knowledge and formations breaking with the Eurocentric and North-Centric tradition of scientific-academic knowledge.